2004
DOI: 10.1128/iai.72.12.6790-6798.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Major Histocompatibility Complex Haplotype Affects T-Cell Recognition of Mycobacterial Antigens but Not Resistance to Mycobacterium tuberculosis in C3H Mice

Abstract: Both innate and adaptive immunity play an important role in host resistance to Mycobacterium tuberculosis infection. Although several studies have suggested that the major histocompatibility complex (MHC) haplotype affects susceptibility to infection, it remains unclear whether the modulation of T-cell immunity by the MHC locus determines the host's susceptibility to tuberculosis. To determine whether allelic differences in the MHC locus affect the T-cell immune response after M. tuberculosis infection, we inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 40 publications
7
41
1
Order By: Relevance
“…However on the susceptible C3H background, the effect of the H-2 b allele on survival after infection with MTB was negligible. 34 Our data are in agreement with findings of Kamath et al in that the H-2-encoded polymorphism(s) is not a major determinant of extreme susceptibility of C3HeB/FeJ to tuberculosis. Indeed, if a major effect of the H-2 locus is on activation of MTBspecific IFN-g producing Th1 cells, as suggested by Kamath et al, it is reasonable to expect that the overall impact of MHC on host resistance would depend on epistatic interactions with other polymorphic gene(s) that determine macrophage responsiveness to the Th1-mediated activation.…”
Section: Chromosome 17 Locussupporting
confidence: 93%
See 1 more Smart Citation
“…However on the susceptible C3H background, the effect of the H-2 b allele on survival after infection with MTB was negligible. 34 Our data are in agreement with findings of Kamath et al in that the H-2-encoded polymorphism(s) is not a major determinant of extreme susceptibility of C3HeB/FeJ to tuberculosis. Indeed, if a major effect of the H-2 locus is on activation of MTBspecific IFN-g producing Th1 cells, as suggested by Kamath et al, it is reasonable to expect that the overall impact of MHC on host resistance would depend on epistatic interactions with other polymorphic gene(s) that determine macrophage responsiveness to the Th1-mediated activation.…”
Section: Chromosome 17 Locussupporting
confidence: 93%
“…31,32 In mice, different alleles at specific H-2 loci affected survival after i.v. infection with virulent MTB, the level of delayed type hypersensitivity (DTH), T cell proliferative response to mycobacterial antigens, and efficacy of antituberculosis vaccination with live attenuated Mycobacterium bovis (BCG), 31 production of IFN-g by mycobacteria-specific T cells, 33,34 as well as production of mycobacteria-specific antibodies. 9,26 Mouse MHC complex contains several genes that participate in processing and presentation of antigenic peptides to cytokine-producing and cytotoxic T cells.…”
Section: Chromosome 17 Locusmentioning
confidence: 99%
“…4; data not shown) (12,14,15). The phenotype of these pulmonary TB10.4 20 -28 -specific CD8 ϩ T cells is consistent with either effector or effector memory T cells (16).…”
Section: A Subset Of Tb104 20 -28 -Specific Cd8 ϩ T Cells In the Lymmentioning
confidence: 84%
“…Deficit of functionally active T cells in the tuberculosis lung lesions of the extremely susceptible C3HeB/ FeJ mice could provide a plausible explanation, as to why the adaptive immunity, although active systemically, failed to control tuberculosis progression in the lungs of the sst1 S mice. However, using the H-2 congenic mouse strains Kamath et al (30) have found that the greater number of the Th1-type T cells in the lungs was controlled by the MHC locus on chromosome 17 and associated with the H-2 b haplotype, which, nevertheless, did not correlate with protection. In contrast, we have shown that progression of tuberculosis infection in the lungs was controlled by the sst1 locus (18), although the sst1 polymorphism did not affect the recruitment of T cells to the lungs of the MTB-infected mice, nor the balance of Th1/Th2 cytokine production.…”
Section: Discussionmentioning
confidence: 98%